2D mapping of hydrogen permeation from a stainless steel membrane. (February 2018) - Miyauchi, Naoya; Hirata, Kenichirou; Murase, Yoshiharu; Sakaue, Hiroyuki A.; Yakabe, Taro; Itakura, Akiko N.; Gotoh, Tetsuji; Takagi, Shoji
Abstract: Hydrogen permeation from a metal surface was visualized by two-dimensional mapping of hydrogen ion desorbed by scanning electron beam irradiation. The sample used was stainless steel containing dislocations of martensite; the sample was 100 μm thick, which is nearly the same as the grain size. One side of the sample was exposed to deuterium gas, and sites of deuterium permeation on the other side were visualized sequentially. There was a good correlation between the patterns of the permeation sites and the grain structure observed in secondary electron images. Graphical abstract: